OpenConMap: A Matlab toolbox for mapping the interior of the unit circle to the exterior of simple closed curves - Kai He; Kai Wang (SoftwareX)
The conformal mapping function from the interior of the complex plane's unit circle to the exterior of any simple closed curve on the real plane finds widespread applications, including the use of complex variable methods in elasticity studies. Our MATLAB toolbox employs numerical methods to solve such conformal mapping functions, applicable to physical domains featuring simple closed curves of arbitrary shapes, and even extending to slit-like structures. Featuring a user-friendly GUI program, the toolbox efficiently computes conformal mapping functions, streamlining the solving process.